Meeting the Medieval in a Digital World - Davis, Matthew Evan; Mahoney-Steel, Tamsyn; Turnator, Ece (Medieval Media Cultures, 2018)
This book looks at the intersection between medieval studies and digital humanities, confronting how medievalists negotiate the "virtual divide" between the cultural artefacts that they study and the digital means by which they address those artefacts. The essays come from medievalists who have created digital resources or applied digital tools and methodologies in their scholarship. Text encoding and analysis, data modeling and provenance, and 3D design are all discussed as they apply to western European medieval literature, history, art history, and architecture